2005
DOI: 10.1017/s1461145705005456
|View full text |Cite
|
Sign up to set email alerts
|

Cortical inhibition in first-degree relatives of schizophrenic patients assessed with transcranial magnetic stimulation

Abstract: Although cortical inhibition deficit has been shown in schizophrenia patients by transcranial magnetic stimulation (TMS), some controversies remain, possibly due to confounding factors such as medication use and clinical state at the time of assessment. First-degree relatives of schizophrenia patients, who share various degrees of genetic vulnerability with the patients, but are free from confounds related to medication and/or florid psychosis, have not been studied to date. We compared 12 relatives with 14 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…Two studies assessing first-episode patients reported increased SP early in the illness. 23,25 However, both first-degree relatives 51 and individuals at risk of SCZ 23 have similar SP durations to controls, suggesting abnormalities may develop with the illness. The disparity between findings in chronic patients is unclear and could reflect subtle differences in methodology.…”
Section: Gaba B -Mediated Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies assessing first-episode patients reported increased SP early in the illness. 23,25 However, both first-degree relatives 51 and individuals at risk of SCZ 23 have similar SP durations to controls, suggesting abnormalities may develop with the illness. The disparity between findings in chronic patients is unclear and could reflect subtle differences in methodology.…”
Section: Gaba B -Mediated Inhibitionmentioning
confidence: 99%
“…29,37,44,69 In contrast, studies have also consistently found increased iSP in medicated and unmedicated chronic SCZ, 37,44,45,70,71 although not in first-degree relatives. 51 As IHI 10 and iSP are mediated by different neuronal populations, these divergent findings are likely to reflect separate pathological mechanisms. Reduced IHI 10 likely reflects deficiency in the neuronal population that mediates inhibition in the target hemisphere (figure 4).…”
Section: Interhemispheric Cortical Connectivitymentioning
confidence: 99%
“…1), von denen 8 keinen Unterschied in der RMT zwischen schizophrenen Patienten bzw. erstgradigen Verwandten [37] und gesunden Kontrollen fanden. In den restlichen Untersuchungen wurde in nur 3 Studien eine niedrigere RMT bei den schizophrenen Patienten im Vergleich zu Kontrollprobanden gefunden, wie es bei einer gestörten Inhibition und höheren Erregungsbildung bei Schizophrenie am ehesten zu erwarten wäre [1,11,18].…”
Section: Motorische Schwelle (Rmt)unclassified
“…In der bereits im Abschnitt über die Ergebnisse mit der Doppelpulstechnik erwähnten Untersuchung mit zwischengeschalteter rTMS wurde lediglich eine nicht signifikante Verlängerung der CSP nach erfolgter rTMS bei unbehandelten und behandelten Patienten im Vergleich zu Kontrollen gefunden [24]. Eine erste Studie an erstgradig verwandten Angehörigen von Schizophreniekranken ergab keine Unterschiede der CSP im Vergleich zur Kontrollgruppe [37]. telten kortikalen hemmenden Prozessen und langsamen, über GABA-B-Rezeptoren mediierten subkortiko-thalamischen inhibitorischen Vorgängen unterschieden werden [17].…”
Section: Kortikale Silent Period (Csp)unclassified
See 1 more Smart Citation